2019
DOI: 10.1111/jocn.14763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oral dietary supplement use in rural older adults

Abstract: Aims and objectives To describe and explore characteristics associated with oral dietary supplement use and identify potential interactions with prescription medications in a sample of rural community‐dwelling older adults. Background Older adults use polypharmacy to help manage chronic diseases. Due to healthcare access disparities, rural older adults may consider dietary supplement use as an alternative approach to maintain health and manage disease. Oral dietary supplement use is expected to increase among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
5
6
0
Order By: Relevance
“…This information is alarming because the Saudi population may be unaware of the adverse effects of dietary supplement overuse. This finding was reported in different populations [17][18][19].…”
Section: Plos Onesupporting
confidence: 86%
See 1 more Smart Citation
“…This information is alarming because the Saudi population may be unaware of the adverse effects of dietary supplement overuse. This finding was reported in different populations [17][18][19].…”
Section: Plos Onesupporting
confidence: 86%
“…National data from the United States and Australia showed that the prevalence of dietary supplement use in adults was approximately 50% in 2011 and 23.5% in 2014-2015, respectively [15,16]. Other studies showed higher prevalences in countries such as Denmark, where the prevalence was 71%, and in the United States [3,[6][7][8][9][10]17]. Compared with the prevalence in Arab countries, that among students in Jordan and UAE was 27% and 39%, respectively [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants in the current study reported that they consume DS to "maintain good health" or to "ensure adequate nutrition" for a statistically significantly higher proportion of older rather than middle-aged adults. These results are congruent with the findings of similar studies [ 1 , 2 , 20 , 24 , 25 , 31 ]. Although the use of DS has been linked to adverse reactions, most users worldwide claim that DS cause no harm [ 24 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study developed by Marcia et al showed that the multicomponent nutrition telemonitoring intervention can improve nutrition status in older adults at risk of undernutrition and improve diet quality and physical activity levels of community‐dwelling older adults. 21 ONSs were found to improve subjective assessments of health‐related QoL in these malnourished older adults. 22 In the United Kingdom, ONSs are mainly administered as part of primary healthcare.…”
Section: Discussionmentioning
confidence: 92%
“…Older adults in the community are often unaware that they have malnutrition, making it difficult for general practitioners to improve malnutrition. The study developed by Marcia et al showed that the multicomponent nutrition telemonitoring intervention can improve nutrition status in older adults at risk of undernutrition and improve diet quality and physical activity levels of community‐dwelling older adults 21 . ONSs were found to improve subjective assessments of health‐related QoL in these malnourished older adults 22 .…”
Section: Discussionmentioning
confidence: 99%